2021
DOI: 10.1016/j.invent.2021.100434
|View full text |Cite
|
Sign up to set email alerts
|

Longer-term effectiveness of eLearning and blended delivery of Mental Health First Aid training in the workplace: 2-Year follow-up of a randomised controlled trial

Abstract: Introduction Evidence relating to long-term outcomes of online education programs is largely lacking and head-to-head comparisons of different delivery formats are very rare. The aims of the study were to test whether eLearning Mental Health First Aid (MHFA) or blended training (eLearning plus face-to-face course delivery), implemented in an Australian public sector workplace, were more effective than a control intervention at 1-year and 2-year follow-up, and whether blended MHFA training was more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…Additionally, the absence of a control group makes it difficult to discern whether observed effects resulted from the course itself or extraneous factors that were not captured in this evaluation. The largely female, well-educated, English-speaking sample is consistent with participant groups from previous MHFA course evaluations [ 20 , 39 ] but limits generalisability outside of this demographic. Relatedly, the vignette of a young female used in this survey, while consistent with national demographic data on the prevalence of NSSI in Australia [ 3 ], may not be relatable to all participants, such as older people and males.…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, the absence of a control group makes it difficult to discern whether observed effects resulted from the course itself or extraneous factors that were not captured in this evaluation. The largely female, well-educated, English-speaking sample is consistent with participant groups from previous MHFA course evaluations [ 20 , 39 ] but limits generalisability outside of this demographic. Relatedly, the vignette of a young female used in this survey, while consistent with national demographic data on the prevalence of NSSI in Australia [ 3 ], may not be relatable to all participants, such as older people and males.…”
Section: Discussionsupporting
confidence: 53%
“…Both interventions resulted in a significant reduction of stigmatising beliefs, but a longer effect was seen by the blended intervention at 6 months follow-up, which was measured by the Opening Minds Scale for Healthcare Providers 44. In a study by Reavley et al 608 public sector employees were randomised into different interventions: two MHFA (Mental Health First Aid) and PFA (Psychological First Aid) online courses and a blended MHFA one 55 56. Significant reduction in stigma scores were found in each intervention groups post training and 1 year follow-up and the Personal Stigma Scale12 showed no significant difference between online and blended courses.…”
Section: Resultsmentioning
confidence: 98%
“…The finding that online interventions might be just as effective as face-to-face interventions was also confirmed by two further randomised controlled studies identified in this review. Reavley et al 55 56 found no significant difference between the effectiveness of blended and purely online interventions on stigmatising attitudes, and a longer-lasting positive effect was found in a blended intervention compared with its face-to-face version in another study 54. These results underline the possible benefits of online interventions over the conventional face-to-face approaches: online interventions are shorter, need no presence of the professionals/trainers, and they have particular potential for the workplace as they can be tailored to participant or workplace needs (ie, can be used anytime during the day), which may also have favourable cost implications.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, a randomized controlled trial (RCT) using Mental Health First Aid (MHFA) blended training course with a one, and two-year follow-up revealed signi cant improvement in knowledge, intentions to help persons with mental illness, and beliefs (34). One interpretation of these results might be the use of mental health rst aid training which provide a comprehensive package including knowledge, available mental health treatment and resources, attitudes and social distance, and intention to help individuals with mental illness.…”
Section: Discussionmentioning
confidence: 99%